Secondary Metabolites from Bryophyllum daigremontianum - Nahar, Kamrun; Khan, Mohammad GU; Rahman, Mohammad S; Hasan, Choudhury M; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2009)
A total of four compounds were isolated from the n-hexane soluble fraction of a methanolic extract of the whole plant of Bryophyllum daigremontianum. The structures of the isolated compounds were elucidated as 11-oxo-epi-Î²-amyrin (1), 21-dehydrodesmosterol (2), 3,4-dihydroxy-cis-cinnamic acid (3), and p-hydroxy-benzaldehyde (4) by high field NMR analyses as well as by comparison with structurally related compounds. Key words: Bryophyllum daigremontianum, Crassulaceae, 11-oxo-epi-Î²-amyrin, 21-dehydrodesmosterol, 3,4-dihydroxy-cis-cinnamic acid, p-hydroxybenzaldehyde. doi: 10.3329/dujps.v7i2.2169 Dhaka Univ. J. Pharm. Sci. 7(2): 141-144, 2008 (December)